Powerplex® ES versus Powerplex® S5 - Casework testing of the new screening kit - Poetsch, Micaela; Kamphausen, Thomas; Bajanowski, Thomas; Schwark, Thorsten; Von Wurmb-Schwark, Nicole (Forensic Science International-Genetics, 2011)
The new Powerplex® S5 Mini STR-System from Promega with the four provided STR loci D18S51, D8S1179, TH01 and FGA as well as the Amelogenin marker (PCR products ranging from 80 to 220 bp not considering the longer FGA fragments) is designed as a screening tool especially in difficult casework samples. To test its suitability we amplified highly degraded DNA from casework samples, which had shown no or only poor results in analyses with the Powerplex® ES kit, as well as artificially degraded DNA or DNA samples containing PCR inhibitors. Despite a tendency for allelic drop-ins in the amplification of highly degraded DNA the Powerplex® S5 kit was a reliable tool for the analysis of casework samples with degraded DNA which gave better results than the Powerplex® ES kit in 64% of analysed swabs. Furthermore, it was especially suitable for the investigation of formalin fixed tissue, tissue samples showing advanced putrefaction or telogen hair samples. However, there was no strict relation between positive Powerplex® S5 results and amplification success with the Powerplex® ES kit. © 2009 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Degraded DNA; PCR; Powerplex; STR